Fermented Dairy Food Intake and Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis - Liang, Zhi; Song, Xiaobiao; Hu, Jiang; Wu, Riga; Li, Pengda; Dong, Zhenyu; Liang, Lu; Wang, Jijun (Frontiers in Oncology, 2022)
It was highly controversial whether fermented dairy foods protects against colorectal cancer (CRC) because of conflicting results from current human epidemiologic studies，we therefore conducted this meta-analysis based on the case-control and cohort studies to estimate the holistic analyses. Finally, total of 7 case-control studies and 10 cohort studies comprising a total of >20,000 cases were incorporated in the quantitative synthesis. Specifically, statistical evidence of significantly decreasing CRC risk in case-control studies was found to be associated with Cheese intake (OR = 0.89, 95% CI = 0.82–0.97), In subgroup analysis, Cheese intake were correlated to lower colon cancer (OR = 0.89, 95% CI = 0.79–1.00) and rectal cancer (OR = 0.86, 95% CI = 0.74–1.00) risk in case-control studies. Furthermore, we also found that the higher intake of yogurt may lower the risk of rectal cancer (OR = 0.75, 95% CI = 0.65–0.88) in cohort studies. The consumption of fermented dairy foods may be relevant to decrease CRC risk in this meta-analysis .